Suppressing Undesired Common-Mode Resonances in Connected Antenna Arrays - Gilmore, J.; Davidson, David (IEEE, 2015)
© 2015 IEEE. This paper presents a design of an antenna feed that suppresses common-mode resonances commonly encountered in connected antenna arrays. The design makes use of symmetrical wideband microstrip-slotline transitions to cancel out common-mode signals, while differential signals will still propagate through. The design is verified using both simulations and measurements of a manufactured prototype. A wide bandwidth and a CMRR > 30 dB is achieved that exceeds the design specifications set out.